Naskah-Naskah Karya K.H. Ahmad Rifa'i Kalisalak di Kabupaten Wonosobo - Nur Laili Noviani; Moch. Lukluil Maknun; Agus Iswanto; Bisri Ruchani (Perpustakaan Nasional RI, 2021)
K.H. Ahmad Rifa’I is one of the scholars in Indonesia who until now has loyal followers and spreads in various regions. One of the da'wah that he taught was to write religious books. The manuscript is still used by the congregation. One of the storage areas for manuscripts by K.H. Ahmad Rifa’i is in Wonosobo, at the house of K.H. Amin Ridlo (Rifa’iyah figure). Some of the manuscripts are thought to have not been disclosed. This study aims to reveal the manuscripts of K.H. Ahmad Rifa’i Kalisalak in Wonosobo kept by K.H. Amen Ridlo. This qualitative descriptive research was carried out with inventory and transmedia activities of the manuscript. Based on the data collection, there were 14 manuscripts by K.H. Ahmad Rifa’i and also the work of his students that have been successfully transferred to the media. These manuscripts contain various titles and themes, and some of them are in accordance with the inventory list that has been compiled by the Rifa’iyah organization.